Green Synthesis of Lauryl Palmitate via Lipase-Catalyzed Reaction - K.M.W. Syamsul; M.A.R. Basyaruddin; Kamaruzaman Jusoff; Salina Mat Radzi; Siti Salhah Othman; Hanina Mohd Noor (IDOSI Publications, 2024)
Volume :11 Number: 4